2020
DOI: 10.1159/000510682
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Evaluating Novel Urinary Biomarkers for Crohn’s Disease

Abstract: <b><i>Introduction:</i></b> Although collecting faeces and blood samples are considered non-invasive methods of monitoring Crohn’s disease (CD), these methods are less preferred by some patients. This study utilized urine as an alternative to evaluate four disease biomarkers in young adults with active CD before and after exclusive enteral nutrition (EEN) therapy. <b><i>Methods:</i></b> Urine samples collected at baseline (W0) and after 8 weeks (W8) of EEN therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Interestingly, circulating IL-8, a pro-inflammatory cytokine, was strongly influenced by ancestry (6% of children had Pakistani ancestry) in our cohorts (25% of variance explained). IL-8 was previously found to be influenced by genetic polymorphisms in an eastern Indian population, potentially driving individual variations in the host’s immune response, in particular to infectious diseases [ 64 ]. Intra-individual factors such as hours of fasting and having a cold gave the expected results: insulin appeared to be the only protein significatively influenced by the hours of fasting and CRP was associated with having a cold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, circulating IL-8, a pro-inflammatory cytokine, was strongly influenced by ancestry (6% of children had Pakistani ancestry) in our cohorts (25% of variance explained). IL-8 was previously found to be influenced by genetic polymorphisms in an eastern Indian population, potentially driving individual variations in the host’s immune response, in particular to infectious diseases [ 64 ]. Intra-individual factors such as hours of fasting and having a cold gave the expected results: insulin appeared to be the only protein significatively influenced by the hours of fasting and CRP was associated with having a cold.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in omics profiles due to factors such as BMI, age, physical activity, fasting time and sampling conditions need to be well characterized in order to interpret subtle changes related to environmental exposures such as air pollution or endocrine-disrupting chemicals, the ultimate goal of recent exposome initiatives [60]. Omics measurements in our study are of great clinical relevance as they provide the basis for the discovery of new biomarkers of multiple medical conditions such as cancer, heart disease, neurological disorders or inflammatory diseases [61][62][63][64]. Here, we provide insight into which omics features are stable within individuals and demonstrate sufficient interindividual variation in order to reduce chance findings when conducting epidemiological studies with follow-up for disease outcomes [16].…”
Section: Discussionmentioning
confidence: 99%
“…A basal level of urinary I-FABP represents the physiological turnover rate of the epithelium, whilst its increment may indicate enterocytes cell damage. In sepsis and IBD, the increased urinary concentration of I-FABP has been confirmed as a reliable biomarker and predictor of disease reactivation, worse prognosis and clinical complications (Ho et al, 2020). Therefore, our study assessed the levels of I-FABP in hospitalised patients with SARS-CoV-2 infection and investigated its role as a predictor of disease severity and poor prognosis.…”
Section: Short Communicationmentioning
confidence: 98%
“…Previous reports have shown that patients with IBD and coeliac disease have significantly higher concentration of circulating iFABP compared with healthy controls (Controls) but evidence has not always been consistent (Additional file 1 : Table 1 ) [ 15 27 ]. The concentration of iFABP in patients with Crohn’s disease has also been shown to correlate with the pro-inflammatory cytokine tumour necrosis factor (TNF)-α and significantly decrease during treatment with anti-TNF-α therapy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently limited literature which has explored responses of iFABP to therapy in patients with Crohn’s disease and coeliac disease and whether these biomarkers might be useful for monitoring changes in small bowel disease activity, and as biomarkers of GFD compliance in the latter group. Furthermore, the value of urinary compared to blood measurements of iFABP, with the former matrix potentially allowing non-invasive and remote monitoring of disease activity, has only been explored in a recent pilot study in adult patients with Crohn’s disease [ 15 ].…”
Section: Introductionmentioning
confidence: 99%